Working together to teach inclusively : a study on the development of a community of practice : a thesis presented in partial fulfilment of the requirements for the degree of Masters in Educational Psychology, Massey University, Distance Learning, New Zealand - Padmasiri, Sneha Samindani (Massey University, 2015)
This qualitative action research project aimed to enhance teachers’ knowledge and practice of inclusion in one secondary school. The study investigated how, through action research, a community of practice (CoP) contributed to the development of teacher knowledge about teaching, learning and inclusion for students with diverse learning needs. A CoP comprising of four teachers, a teacher aide and the researcher was established and began their action research with an exploration of students' perspectives of school. Student perspectives became the starting point for teachers to explore the meaning of inclusive education and its implications for teaching and learning, including the roles and responsibilities of staff. Perspectives of students also became the basis for teachers to apply the knowledge of inclusive practice gained in the CoP to their daily teaching. Teacher and student interviews, student surveys, CoP meeting minutes and informal conversation data were examined to find how within the CoP teachers responded to their students' perspectives; how teachers co-constructed knowledge about inclusive teaching practice; and how teachers changed their classroom practice as a result of knowledge sharing. Results show that through their participation in the CoP, teachers' understandings about inclusion were affirmed and developed further; teachers responded to students' comments about school by developing their teaching practice to attend to students' strengths and needs for support; teachers shared knowledge of inclusive teaching practices within the CoP and planned to share knowledge beyond the CoP; and there was some indication of students feeling positive effects from developments in the CoP. The study indicates the importance of using school staff's shared knowledge as a resource when promoting inclusion in schools and providing teachers’ time to collaborate and share knowledge as part of their professional learning.
Keywords: Inclusive education; Communities of practice